Changing security agendas and the Third World - Pettiford, Lloyd, 1966-; Curley, Melissa, 1971- (London ; New York : Pinter, 1999)
"Security has long been a central organizing concept of International Relations. Until the 1980s students of the discipline understood its simple essence in terms of the arms race and balances of power. Then, reflecting changes encouraged by both the inter-paradigm debate and the so-called third debate, security underwent radical reconsideration. The many attempts to redefine the concept led to a proliferation of terms such as true security, global security, common security and environmental security. However, these terms have often been used in confusing and contradictory ways."--BOOK JACKET. "In attempting to help students deal with this confusion, this book outlines the theoretical tools at the disposal of students for their own rethinking of the concept of security. The book will help students wishing to seriously engage with IR's security debate at whatever level, and draws its own conclusions as part of this debate."--BOOK JACKET.
Introduction: Contemporary Insights on Security -- 1. Rethinking the Third World -- 2. Opening the Can of Worms: Realism to Neorealism -- 3. Critical Theory and Postmodernism: The Challenges -- 4. Environmental/Ecological Philosophies and Security -- 5. Engaging with Other Fields and Disciplines -- 6. Security and Development: Exploring Conceptual and Practical Linkages -- 7. Security and Sustainable Development -- Conclusions: The Future of Security? -- Afterword: Signing the Swamplands / Stephen Chan.
Includes bibliographical references and index.
Keywords: Security, International; Sustainable development; Developing countries -- Foreign relations